THE INFLUENCE OF ACCOUNTING UNDERSTANDING, ACCOUNTING INFORMATION SYSTEM QUALITY AND SUPERVISORY BOARD FUNCTION ON THE QUALITY OF FINANCIAL REPORTING OF VILLAGE-OWNED ENTERPRISES: A Study on Village-Owned Enterprises in Tabanan District - Ristyani, Ni Kadek Yuna; Werastuti, Desak Nyoman Sri; Adiputra, I Made Pradana (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the influence of accounting understanding, accounting information systems quality, and supervisory board function on the quality of financial reporting of Village-Owned Enterprises in Tabanan District. The background of this study is the phenomenon of delays and low-quality financial reports, which have implications for the quality of Village-Owned Enterprise financial reporting. These problems are influenced by managers' limited understanding of accounting, suboptimal utilization of accounting information systems, and weak oversight functions. The novelty of this study lies in the integration of these three main variables into the quality of Village-Owned Enterprise financial reporting, a previously rarely studied study. This study used quantitative methods. The research data were sourced from primary data through questionnaires distributed to managers. The population of this study was 12 Village-Owned Enterprises in Tabanan District. The sampling technique used purposive sampling, resulting in a sample of 7 Village-Owned Enterprises in Tabanan District with 42 Village-Owned Enterprise managers as respondents. The results indicate that accounting understanding, accounting information system quality, and supervisory board function have a positive and significant effect on the quality of Village-Owned Enterprise financial reporting.